(untitled) (Research, Society and Development, 2022)
This research is about the experiences and challenges of mothers when returning to work after maternity leave. Thus, the objective was to analyze experiences after the return of maternity leave among workers of a Brewery in the northeast region of Brazil. Therefore, a descriptive study with a qualitative approach was carried out, in order to obtain more data, enriching the knowledge and understanding of the subject in question. Three women mothers and professionals over 18 years of age were included, who returned to work after being away on maternity leave in the last five years, who developed their work activities in that company during the study period and who voluntarily agreed to participate in the research. Data analysis was based on the content of the reports obtained through interviews, and their discussion was carried out in accordance with the theoretical foundations of the bibliographic research. The results showed that despite the strengthened legislation and, often, improved benefits, many women are unable to organize themselves in a way to reconcile motherhood and work due to factors ranging from the emotional to the socioeconomic. Thus, it was concluded that there are still great problems and challenges to be faced. It will be shown that during the period of primary concern, some feelings such as impotence, fear, worry, anxiety and great tension develop in women.